sin(x+y)=sin(x)*cos(y)+cos(x)*sin(y)

sin(x-y)=sin(x)*cos(y)-cos(x)*sin(y)

cos(x+y)=cos(x)*cos(y)-sin(x)*sin(y)

cos(x-y)=cos(x)*cos(y)+sin(x)*sin(y)

sin(2x)=2sin(x)cos(x)

cos(2x)=cos^2(x)-sin^2(x)

sin(x+y)-sin(x-y)=2sin(x)cos(y)

sin(x+y)-sin(x-y)=2cos(x)sin(y)

cos(x+y)+cos(x-y)=2cos(x)cos(y)

cos(x+y)-cos(x-y)=-2sin(x)sin(y)

sin(x)+sin(y)=2sin((x+y)/2)cos((x-y)/2)

sin(x)-sin(y)=2cos((x+y)/2)sin((x-y)/2)

cos(x)+cos(y)=2cos((x+y)/2)cos((x-y)/2)

cos(x)-cos(y)=-2sin((x+y)/2)sin((x-y)/2)

tg(2x)=(2tg(x))/(1-tg^2(x)) gdy cos(x) różne od zera i cos(2x) różne od zera

ctg(2x)=(ctg^2(x)-1)/(2ctg(x)), gdy sin(x) różne od zera i sin(2x) różne od zera

tg(x+y)=(tg(x)+tg(y))/(1-tg(x)tg(y))

tg(x-y)=(tg(x)-tg(y))/(1+tg(x)*tg(y))

ctg(x-y)=(ctg(x)*ctg(y)+1)/(ctg(x)-ctg(y))

ctg(x+y)=(ctg(x)*ctg(y)-1)/(ctg(x)+ctg(y))